PKM PELATIHAN RETORIKA DAN FARDHU KIFAYAH UNTUK ANGKATAN MUDA MUHAMMADIYAH DI KOTA BINJAI - Hasanuddin Hasanuddin; Irvan Irvan; Surya Wisada Dachi; Rahmat Mushlihuddin (IHSAN : JURNAL PENGABDIAN MASYARAKAT, 2019)
AbstractThis PKPM activity will be carried out for the Muhammadiyah Youth Force in Binjai City in general, specifically for PRM Kartini. The purpose of this activity is to provide rhetoric and fardhu kifayah training for AMM as part of the regeneration activities carried out among AMM, where AMM has the function and role as a Pioneer, Implementation and Refinement of the Muhammadiyah Association. The activity that will be carried out is to provide a theory of rhetoric and fardhu kifayah in 2 (two) meetings in 1 (one) month, then the implementation of practice in 2 (two) meetings in 1 (one) month. The PKPM activity is divided into two activities, so the specific objectives of the PKPM activity are divided into two, namely: 1) rhetorical activity, training participants from the AMM can assist the PRM in implementing activities on the branch as a moderator or protocol in routine recitation activities of the Muhammadiyah Branch, activities recitation in the month of Ramadan, 2) the implementation of fardhu kifayah at the Muhammadiyah Branch, training participants from the AMM can help PRM in carrying out fardhu kifayah activities in the branch. While other objectives are expected AMM can play an active role in each Muhammadiyah Branch, and can become a successor cadre of society. Keywords: Fardhu Kifayah, Rhetoric, Branches, AMM